ANALYSIS AND MODELING OF TERMINAL POSITION ERROR OF PARALLEL MANIPULATOR BASED ON MDH METHOD - ZHANG YunFan; CHEN JinJie; HAO XinLong (Jixie qiangdu)
In this paper, a typical component in parallel manipulator--the parallelogram mechanism, is studied and the terminal position error that results from the change in length of each connecting rod is analyzed. Taking a two-degree-of-freedom manipulator as the research object, the Modified D-H method is used to solve the forward kinematics, and the prediction model of terminal position in consideration of the inaccuracy by parallelogram mechanism is established. The corresponding simulation experiment of error distribution is carried out by using the Monte-Carlo method in Matlab, and the distribution characteristics of the manipulator’s terminal position error under different machining tolerance are obtained, then the accuracy of the prediction model is verified by the prototype experiment. The research shows that the joint angles of parallel manipulators calculated using this method are more accurate, which improves the accuracy of terminal position modeling.